Optimalisasi Pembelajaran Bahasa Indonesia dengan Integrasi TPACK dan Pendekatan Saintifik melalui Project Based Learning pada Teks Tanggapan untuk Siswa Kelas 9 SMP - Handayani, Sulikah Tri; Saputra, Bachtiar Adi (TSAQOFAH, 2024)
Learning Indonesian requires a holistic approach to facilitate students' in-depth understanding of the language, culture and communication skills. This article explains efforts to optimize Indonesian language learning for grade 9 junior high school students through the integration of technological content pedagogical knowledge (TPACK) and scientific approaches. Implementation is carried out through a project-based learning (PBL) model on response texts, with the aim of improving the quality of learning and students' literacy skills. This research adopts an experimental research design by integrating two main approaches, namely technological content pedagogical knowledge (TPACK) and a scientific approach, through a project-based learning (PBL) model. This experimental design was chosen to allow evaluation of the impact of combining the two approaches on students' literacy understanding and skills. The results of learning evaluation using the Project Based Learning (PBL) method show very satisfactory achievements. Of the 31 students involved in the research, 26 of them managed to achieve or even exceed the Minimum Completeness (KKM) with a class average score of 95. This indicates that the implementation of PBL has succeeded in having a positive impact on students' understanding of Indonesian language material at this level. 9th grade of junior high school. Based on this, it can be concluded that students who scored above the KKM have exceeded the percentage of 85%, namely 26 students. The successful implementation of TPACK and the scientific approach through PBL in Indonesian language learning depends on the support of all parties, careful planning, appropriate selection, and supporting strategies such as ice breaking.